On the secure creation, organisation and discovery of topics in distributed publish/subscribe systems. (21st October 2008) - Pallickara, Shrideep; Fox, Geoffrey; Gadgil, Harshawardhan
Publish/Subscribe infrastructures have gained significant traction recently with several specifications such as the Java Message Service (JMS), WS-Eventing and WS-Notification. In this paper we present a scheme for the secure organisation and discovery of topics in distributed publish/subscribe systems. The scheme also addresses security related issues such as authorisation and provenance in the discovering these topics. Our experimental results demonstrate the feasibility of this framework. We have also included a scheme for the organisation and discovery of topics that have hierarchical relationships and those that are part of a collection of topics in dynamic, high-flux publish/subscribe environments.